Pressure Ulcer Risk in the Incontinent Patient: Analysis of Incontinence and Hospital-Acquired Pressure Ulcers From the International Pressure Ulcer Prevalence™ Survey. Issue 3 (May 2016) - Lachenbruch, Charlie; Ribble, David; Emmons, Kirsten; VanGilder, Catherine
Abstract : PURPOSE: To measure the prevalence of incontinence in the 2013-2014 International Pressure Ulcer Prevalence (IPUP) surveys and determine the relative risk of developing a facility-acquired pressure ulcers (FAPUs) by stage and by Braden Scale score groupings. DESIGN: The IPUP survey is an observational, cross-sectional cohort database designed to determine the frequency and severity of pressure ulcers in various populations. SUBJECTS AND SETTING: The survey includes acute care (91.4%), long-term acute care (1.7%), rehabilitation patients (1.7%) and long-term care residents (5.2%). Geographic distribution included 182, 832 patients in the United States, 22, 282 patients in Canada, and the rest of the world, primarily in Europe and the Middle East. METHODS: We analyzed data from the 2013 and 2014 IPUP surveys to better understand the relationship between incontinence and the frequency and severity of FAPUs. The IPUP survey is an annual voluntary survey of patients who are hospitalized or who reside in long-term care facilities. Data were collected over a 24-hour period within each participating facility. Data collection included limited demographics, presence and stage of pressure ulcers, and pressure ulcer risk assessment score (Braden Scale for Pressure Sore Risk, Braden Q, Norton, Waterlow, and others). In addition, data were collected on pertinent pressure ulcer risk factors including the number of linen layers, use of a pressure redistributing surface, adherence to repositioning schedule, and whether moisture management was provided in the last 24 hours. We aggregated data by urinary, urinary catheter, fecal, fecal management system, double (urinary and fecal), and ostomy incontinence category. If patients were managed by indwelling urinary catheter or fecal management systems, they were considered incontinent in this analysis. In order to analyze ulcers likely to be affected by incontinence, we defined a subset of ulcers as Relevant Pressure Ulcers, which are ulcers that are facility-acquired, non–device-related, and located in the pelvic region. RESULTS: We analyzed 176, 689 patients based on data collected between 2013 and 2014. Slightly less than half (n = 83, 800; 47%) of patients did not have incontinence, and 92, 889 (53%) were deemed to be incontinent. The prevalence of pressure ulcers was 4.1% for continent patients and 16.3% for incontinent patients; the prevalence of FAPUs was 1.6% and 6.0%, respectively. The relative risk for PU development in incontinent patients was higher than predicted by the Braden Scale risk score. As wound severity increased, the odds ratios for pressure ulcer development for incontinent patients versus continent patients also increased, especially in patients with fecal incontinence. CONCLUSIONS: Incontinent patients had higher Braden Scale scores and higher overall and FAPU prevalence. Incontinence was associated with an increased risk for all pressure ulcers, but especially full-thickness injuries.